Uterine rupture in a term pregnancy after a previous uterine artery embolization to manage a large fibroid. A case report - Heba Abu Saleem; Nouf Albalwi; Lina Ba'Abbad (Elsevier, 2023)
Uterine artery embolization (UAE) is an effective minimally invasive alternative to surgery for the treatment of symptomatic uterine fibroids. Uterine rupture is an obstetrical emergency that requires early diagnosis and prompt management to improve perinatal and maternal outcomes.A 33-year-old woman at 37 weeks of gestation who had had previous two uncomplicated vaginal deliveries at term presented with abdominal pain and rupture of membranes. The patient had undergone UAE for the management of a large anterior wall uterine fibroid three years prior to conception. Vaginal examination revealed cord prolapse and ultrasound showed negative fetal heart. Intrauterine fetal demise with cord prolapse was diagnosed. After admission the patient developed vaginal bleeding and features of hypovolemic shock. Urgent laparotomy revealed a ruptured uterus with a large hemoperitoneum and dead fetus in the abdominal cavity.Obstetricians should be attentive to the possibility of a spontaneous uterine rupture in pregnant women who have previously undergone UAE for the management of a uterine fibroid.